Islamic Law Analysis of Sadd Adz-Dzari'ah on The Conversion of Agricultural Land in Karanganyar Regency - Rizki Ajudiansyah; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2024)
This article reviews in depth the aspects of Islamic law related to the conversion of agricultural land, focusing on the principle of Sadd Adz-Dzari'ah. This principle is the main foundation of this research, playing an important role in regulating the process of land transformation and setting legal boundaries that must be obeyed. Through a case study conducted in Karanganyar Regency, this research aims to evaluate the application of the Sadd Adz-Dzari'ah principle in the context of agricultural land conversion and provide an in-depth understanding of the principles, to assess its implementation in agricultural land conversion in Karanganyar Regency, to analyze the social, economic and environmental impacts of land use change and propose policies to the local government to improve justice and sustainability, taking into account Islamic values. The research method is based on a qualitative approach with in-depth interviews and document analysis. The collected data were analyzed using content analysis techniques to identify patterns and main themes related to the application of Sadd Adz-Dzari'ah principles in agricultural land conversion. The results showed that the Sadd Adz-Dzari'ah rule has a central role in regulating and guiding the process of conversion of agricultural land into housing within the framework of Islamic law. This research highlights that the conversion of agricultural land to housing is not just a physical change, but also involves significant social, economic and environmental aspects. Social impacts include changes in the lifestyle of rural communities, while economic impacts include aspects of increased land value and changes in livelihoods. Environmental impacts include vulnerability to land degradation and loss of biodiversity. This research is expected to make a significant contribution to the understanding of the relevance and implementation of the Sadd Adz-Dzari'ah principle in the context of rural land use change. It also aims to provide a foundation for better policies that are in line with Islamic values.